Pharmacological Evaluation Of An Aqueous Extract Of Orthosiphon Stamineus (Misai Kucing). For Its Diuretic Property - Ibrahim, Hj. Mohd Kasim (1981)

(untitled)
The diuretic property of o. starnineus was evaluated in unananesthetised, male albino rats. Twelve rats, divided into three groups of four were used. Une representing the controls, tredted with distilled water(1ml/kg), tne second Group, treated with frusemide (l0mg/kg) as the standard and finally the third' group was treated with the v. stamineus extract, all were injected intraperi toneal1y.